Analisis rantai pasok pengembangan agroindustri abon ikan lele di Kabupaten Jember - Yuli Wibowo; Herlina Herlina; Siswoyo Soekarno; Andi Eko Wiyono; Haidar Ali (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Shredded catfish is one of the leading agro-industrial products with development potential in Jember Regency. Shredded catfish is an alternative processed fish product with many enthusiasts and is easily marketed. The shredded catfish processing business has great prospects because catfish meat is readily available, and people are increasingly consuming fish instead of red meat like beef. The high catfish production in Jember Regency supports the potential for agro-industrial product development in the fisheries sector. This study aims to analyze the supply chain of catfish abon agroindustry in Jember Regency. This study consists of several stages that are systematically arranged using relevant methods, including (i) identifying the supply chain structure and the role of supply chain actors using descriptive analysis methods, (ii) determining the most dominant supply chain actors using the Interpretive Structural Modeling (ISM) method, and (iii) formulating a supply chain development strategy using the Analytical Hierarchy Process (AHP) method. The results showed that the supply chain structure of shredded catfish involves three main members: suppliers, producers, and consumers. Catfish suppliers provide quality raw materials, producers process raw materials into ready-to-consume products, producers act as distributors who manage logistics and distribution, producers act as retailers who sell products to consumers, and consumers create market demand. The consumer is the most dominant actor in the shredded catfish supply chain. Consumers drive demand and determine the success of the product in the market. Developing new markets through digital marketing using social media is the most optimal and dominant catfish-shredded supply chain development strategy because it has the highest priority.